ALFOS ENERGY (ALTERNATIVE ENERGY FOR ANGKRINGAN ENTREPRENEURS) SEBAGAI USAHA ZERO POLLUTION ASAP ARANG DAN LAMPU TEMPEL PADA WARUNG ANGKRINGAN - Iskandar, Muhamad; Sisilia, Maisel Priskila; Sutiani, Nurlia; Habibullah, Ahmad; Khairudin, Mohammad (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This paper presents experimental and implementation of solar cell for alternative energy source of angkringan (traditional food stalls) in Yogyakarta province. The angkringan is a famous place among the stalls selling food and constantly visited by most of people. Implementation of solar cell has two functions, namely as a source of alternative energy for traditional food stalls and to keep a comfortable environment for fans culinary. Visitor feel comfort when they are not disturbed by smoke pollution outboard lamps and wood charcoal are usually used in the angkringan. The results show the resilience of solar cell can cover between 12 hours to 14 hours, and depending on the load used to turn other device besides substituting for wood charcoal and lighting. The tool resiliences are proportional to the operating time of food stall that usually requires lighting from 17:30 hours until 00:30 or more. Advantages of this tool also is with the mobile cart can make easier for entrepreneurs to find a strategic place for gaining benefit without relying on PLN power. With an affordable cost of solar cell can be applied to a food stall that could be an alternative solution to maintain a healthy and comfortable environment as well as getting the optimum benefit.